ENTREVISTA COM PROFESSORAS (ES) DE FILOSOFIA DO ENSINO SUPERIOR DO CEARÁ (Bloco II) - Marinho, Cristiane Maria; Silva, Francisco José da; Oliveira, Camila do Espírito Santo Prado de; Sousa, Antônio Alex Pereira de; Lima, Paulo Willame Araújo de (Revista Dialectus - Revista de Filosofia, 2023)
ENTREVISTA COM PROFESSORAS (ES) DE FILOSOFIA DO ENSINO SUPERIOR DO CEARÁ – BLOCO II Com: Cristiane Maria Marinho, Francisco José da Silva, Camila do Espírito Santo Prado de Oliveira Por: Antônio Alex Pereira de Sousa, Paulo Willame Araújo de Lima